(untitled) (Coloquio Interdisciplinario de Posgrado UPAEP, 2019)
The generation of electric power is one of the main problems at present, and although solutions have been sought by several methods, it is difficult to meet the demand and do so with activities of low environmental impact. One proposal is the use of urban solid waste for the generation of energy since this way two environmental problems can be covered. This work is based on the improvement of a solid waste to electric energy conversion system through a thermolysis reactor in which an intelligent control system will be applied for the optimization of the products to be obtained in addition to the inclusion of a concentration system of solar energy for the incineration of waste.